2019
DOI: 10.5588/ijtld.18.0201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neonatal bacille Calmette-Guérin on the tuberculin skin test reaction in the first 2 years of life

Abstract: Latent tuberculous infection (LTBI) is an important reservoir of disease reactivation that is sufficient to generate new cases for decades. The tuberculin skin test (TST) is an important tool to diagnose LTBI; however, neonatal bacille Calmette-Guérin (BCG) vaccination may impact interpretation of TST data. O B J E C T I V E S : To analyse the effect of the neonatal BCG vaccine on TST reaction in the first 2 years of life in children with no identified contact with tuberculosis (TB). D E S I G N : This was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Likewise, two meta-analyses showed that vaccination with BCG significantly increases the likelihood of a positive TST [ 20 , 21 ]. In contrast, a cross-sectional study in Brazil has shown that BCG had a low impact on TST in children <2 years old without apparent contact with TB patients [ 10 ], and a cohort study in India demonstrated that no infant who received BCG vaccination within the first month of life had a TST reaction size greater than 10 mm [ 11 ]. Two studies, however, differ from ours in vaccine strain, administration method, age group tested, environmental mycobacteria, and sample size, thus leading to the challenges of interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, two meta-analyses showed that vaccination with BCG significantly increases the likelihood of a positive TST [ 20 , 21 ]. In contrast, a cross-sectional study in Brazil has shown that BCG had a low impact on TST in children <2 years old without apparent contact with TB patients [ 10 ], and a cohort study in India demonstrated that no infant who received BCG vaccination within the first month of life had a TST reaction size greater than 10 mm [ 11 ]. Two studies, however, differ from ours in vaccine strain, administration method, age group tested, environmental mycobacteria, and sample size, thus leading to the challenges of interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…One major factor is the bacilli Calmette-Gue ´rin (BCG) vaccination, which reduces the specificity of the TST test and can lead to unnecessary treatment for those without TB Infection [6][7][8][9]. Some studies, however, presented conflicting results, indicating that BCG vaccination has only a limited effect on TST among infants [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, immunization (BCG vaccine) is performed at birth, which is mandatory, but it is known to confer only immunity to severe forms of tuberculosis. Thus, all Brazilians are vaccinated, and this influences the TST results since the vaccine is active for ten years after its application (24) . Conversely, this study is composed of adult or young adult patients, being questioned on the first visit the possibility of revaccination, being negative in all cases (TABLE 3) (23,25,26) .…”
Section: Discussionmentioning
confidence: 99%
“…TST reactivity among BCG-vaccinated population is affected by multiple factors such as the strain and dose of BCG vaccine, 29 30 the method of vaccination, 31 the number of BCG doses, 32 33 age at vaccination, 34 and the time interval since BCG vaccination. 34 35 36 37 Kurtz et al 37 assessed the effect of neonatal BCG on TST reaction in the first 2 years of life in children without TB exposure. There was a significant decrease in mean TST reaction with an increase in age.…”
Section: Discussionmentioning
confidence: 99%